2019
DOI: 10.1103/physreva.100.012709
|View full text |Cite
|
Sign up to set email alerts
|

Universality in a one-dimensional three-body system

Abstract: We study a heavy-heavy-light three-body system confined to one space dimension. Both binding energies and corresponding wave functions are obtained for (i) the zero-range, and (ii) two finiterange attractive heavy-light interaction potentials. In case of the zero-range potential, we apply the method of Skorniakov and Ter-Martirosian to explore the accuracy of the Born-Oppenheimer approach. For the finite-range potentials, we solve the Schrödinger equation numerically using a pseudospectral method. We demonstra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 56 publications
(102 reference statements)
4
38
0
Order By: Relevance
“…Moreover, lower dimensional systems, such as three fermionic particles confined to two dimensions, display surprising universal phenomena like the so-called "super Efimov effect" [3,4,5,6]. Recently, some of the authors have demonstrated that in one dimension, universality in a mass-imbalanced three-body system is not only present in the discrete spectrum [7], but universal three-body bound states also occur in the continuum as induced by excited two-body resonances [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, lower dimensional systems, such as three fermionic particles confined to two dimensions, display surprising universal phenomena like the so-called "super Efimov effect" [3,4,5,6]. Recently, some of the authors have demonstrated that in one dimension, universality in a mass-imbalanced three-body system is not only present in the discrete spectrum [7], but universal three-body bound states also occur in the continuum as induced by excited two-body resonances [8].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Ref. [7] three-body energies and the corresponding wave functions of the bound states are computed by representing the Hamiltonian as a sparse matrix, and using a Krylov subspace method to determine its lowest eigenvalues and the corresponding eigenvectors. However, with an increasing number of grid points in each dimension, the matrices and vectors grow rapidly: The three-body problem in d space dimensions yields a 2d-dimensional linear eigenvalue problem after removing the center-of-mass degree of freedom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-body recombination occurs throughout physics from ultracold plasmas [33] to chemistry [34] and astrophysics [35] and has been extensively studied in ultracold atoms [22,[36][37][38][39][40][41]. Moreover, the rich physics of idealised three atom systems in tightly confining traps is currently the target of intensive theoretical studies [42][43][44][45][46][47], while experiments are presently lacking.…”
mentioning
confidence: 99%
“…and remains finite also in the limit q 0 → 0, due to equation (12). First, we discuss the integrals I 1 and I 4 .…”
Section: Type-ii Potentials: Fmentioning
confidence: 99%